Preliminary study of highly cross-linked hyaluronic acid-based combination therapy for management of knee osteoarthritis-related pain - Palmieri B; Rottigni V; Iannitti T (Dove Medical Press, 2013)
Beniamino Palmieri,1,2 Valentina Rottigni,1,2 Tommaso Iannitti2,31Department of General Surgery and Surgical Specialties, University of Modena and Reggio Emilia Medical School, Surgical Clinic, Modena, Italy; 2Poliambulatorio del Secondo Parere, Modena, Italy; 3Department of Physiology, School of Medicine, University of Kentucky Medical Center, Lexington, KY, USABackground: Hyaluronic acid has been extensively used for treatment of knee osteoarthritis due to its anti-inflammatory properties and its ability to act as a synovial lubricant. Furthermore, it has found application in combination with other drugs in the dermatological field and in pre-clinical studies in animal models of osteoarthritis. Experimental evidence suggests that a combination of this macromolecule with other drugs may act as a slow-release depot. However, to date, to the best of our knowledge, no one has tested local intra-articular delivery of highly cross-linked hyaluronic acid combined with bisphosphonate or nonsteroidal anti-inflammatory drugs for management of knee osteoarthritis pain in the clinical setting. The aim of the present randomized double-blind study was to investigate, for the first time, the effect of a highly cross-linked hyaluronic acid, Variofill®, alone or in combination with diclofenac sodium or sodium clodronate, for management of bilateral knee osteoarthritis-related pain.Methods: Sixty-two patients with symptomatic bilateral medial tibiofemoral knee osteoarthritis (Kellgren–Lawrence grade II and III) and pain in both knees corresponding to a daily visual analog scale (VAS) score ≥ 30 in the month before the beginning of the study were included in this investigation. Patients were divided into three groups: group 1, treated with an injection of hyaluronic acid alone (66 mg) into each knee; group 2, treated with an injection of hyaluronic acid (49.5 mg) plus diclofenac sodium (5 mg) into each knee; group 3, treated with an injection of hyaluronic acid (49.5 mg) plus sodium clodronate (5 mg) into each knee. Patients also underwent blood tests for measurement of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) immediately before and at 6-month follow-up.Results: Hyaluronic acid alone and in combination with sodium clodronate or diclofenac sodium produced a significant improvement in mean VAS pain score at 3 and 6-month follow-up. At 6-month follow-up, therapy with hyaluronic acid plus sodium clodronate was the most beneficial in terms of percentage improvement in VAS pain score. A significant improvement in ESR and CRP was observed at 6-month follow-up in each treatment group. No significant difference was observed when the percentage change from baseline related to these parameters was compared among the groups. No dropout was observed in any group. No serious adverse events were observed.Conclusion: Further studies are necessary to determine the effect of a therapy based on hyaluronic acid combined with diclofenac sodium or sodium clodronate in larger cohorts of patients affected by knee osteoarthritis and in longer-term follow-up.Keywords: osteoarthritis, hyaluronic acid, bisphosphonate, sodium clodronate, nonsteroidal anti-inflammatory drug, diclofenac sodium, viscosupplementation, combination therapy, knee, pain